An evaluation of the Unciano Colleges of Antipolo Academic Health Library Collection and Services based on users' assessment - Santos, Vladimir Ross C.; Timoteo, Christine B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2008)
Since an academic health library functions as a vital unit for the continuing education of students and faculty members, a deep analysis of its collection and services has to be done in order to make the necessary changes to meet the library users' demands. It is in this direction that this study focused on the evaluation of the collection and services based on users' assessment of the Unciano Colleges of Antipolo Academic Health Library.
Aside from the faculty members, a total of 268 students were surveyed. The questionnaire used in this study was patterned after Alberto's (The Provincial Library: an evaluation of its library collection and services, 1972) with some revisions. The said questionnaire was divided into 4 parts: Respondent's Profile, Information Needs, Library Collection and Services and Users' Rating of its Collections and Services.
The data gathered from the survey questionnaire revealed that: (a) 55 (95) and 154 (57.5) of the faculty members and students, respectively, frequently visit the library (b) only 19 (32.7) and 80 (29.9) faculty members and students respectively, use the school library on a daily basis; (c) 58 (100) and 268 (100 percent) of the faculty members and students respectively, are aware of the electronic materials as well as who said that this informational format is greatly needed; (d) majority of the students acquire information through the Internet (127 or 47 percent) while faculty members acquire information through books, manuals, etc. (17 or 29.3); (f) 230 (85.8) of students said that their purpose in going to the library is just to read newspapers while 56 (96.6) of the faculty members has the same purpose as that of the students'; (g) 268 (100 percent) of the students need library materials for personal reading while 58 (100) of the faculty members chose need library materials for school work; (h) 27 (46.6) of the faculty members rated the staff inside the library as moderately helpful while 120 (44.8) of the students gave the same rating.
Recommendations included the development of a Collection Development Policy as well as Marketing Plan for the library in order for it to be heard by the school's administration.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Unciano College of Antipolo Academic Health Library -- Evaluation; Libraries -- User satisfaction -- Philippines; Academic libraries -- Use studies; Needs assessment -- Philippines